Risk Factors for Severe Acute Respiratory Syndrome Coronavirus 2 Infection in Hospital Workers: Results From a Screening Study in New Jersey, United States in Spring 2020. (31st October 2020) - Barrett, Emily S; Horton, Daniel B; Roy, Jason; Xia, Weiyi; Greenberg, Patricia; Andrews, Tracy; Gennaro, Maria Laura; Parmar, Veenat; Russell, William D; Reilly, Nancy; Uprety, Priyanka; Gantner, John J; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is a critical concern among healthcare workers (HCWs). Other studies have assessed SARS-CoV-2 virus and antibodies in HCWs, with disparate findings regarding risk based on role and demographics. Methods: We screened 3904 employees and clinicians for SARS-CoV-2 virus positivity and serum immunoglobulin (Ig)G at a major New Jersey hospital from April 28 to June 30, 2020. We assessed positive tests in relation to demographic and occupational characteristics and prior coronavirus disease 2019 symptoms using multivariable logistic regression models. Results: Thirteen participants (0.3%) tested positive for virus and 374 (9.6%) tested positive for IgG (total positive: 381 [9.8%]). Compared with participants with no patient care duties, the odds of positive testing (virus or antibodies) were higher for those with direct patient contact: below-median patient contact, adjusted odds ratio (aOR) = 1.71 and 95% confidence interval [CI] = 1.18–2.48; above-median patient contact, aOR = 1.98 and 95% CI = 1.35–2.91. The proportion of participants testing positive was highest for phlebotomists (23.9%), maintenance/housekeeping (17.3%), dining/food services (16.9%), and interpersonal/support roles (13.7%) despite lower levels of direct patient care duties. Positivity rates were lower among doctors (7.2%) and nurses (9.1%), roles with fewer underrepresented minorities. After adjusting for job role and patient care responsibilities and other factors, Black and Latinx workers had 2-fold increased odds of a positive test compared with white workers. Loss of smell, taste, and fever were associated with positive testing. Conclusions: The HCW categories at highest risk for SARS-CoV-2 infection include support staff and underrepresented minorities with and without patient care responsibilities. Future work is needed to examine potential sources of community and nosocomial exposure among these understudied HCWs. Abstract : In a screening of 3904 New Jersey hospital employees and clinicians, 9.8% tested SARS-CoV-2 virus or IgG antibody positive. In multivariable models, direct patient contact, job role, and black and Latinx race/ethnicity were all associated with positive test results.